SAURON: The Wallace Observatory Small AUtonomous Robotic Optical Nightwatcher. (16th May 2017) - Kosiarek, M.; Mansfield, M.; Brothers, T.; Bates, H.; Aviles, R.; Brode-Roger, O.; Person, M.; Russel, M.
Abstract: The Small AUtonomous Robotic Optical Nightwatcher (SAURON) is an autonomous telescope consisting of an 11-inch Celestron Nexstar telescope on a SoftwareBisque Paramount ME II in a Technical Innovations ProDome located at the MIT George R. Wallace, Jr. Astrophysical Observatory. This paper describes the construction of the telescope system and its first light data on T-And0-15785, an eclipsing binary star. The out-of-eclipse R magnitude of T-And0-15785 was found to be 13.3258 ± 0.0015 R magnitude, and the magnitude changes for the primary and secondary eclipses were found to be 0.7145 ± 0.0515 and 0.6085 ± 0.0165 R magnitudes, respectively.